Impact of Work-Sharing on the Performance of Production Line With Heterogeneous Workers - Pasupa, Thanatat; Suzuki, Sadami (International Journal of Industrial Engineering and Management, 2019)
This study addresses the problem of Dynamic Line Balancing (DLB) in a two-stage production assembly tandem line where there are worker differences. This study examines the dynamic decision rules for workers to operate under DLB with a low level of work in process (WIP), in the constant work-in-process (CONWIP) system. We develop a new dynamic decision rule, the Smallest R No Starvation-II (SRNS-II), to maximize the throughput of the system. Results showed that DLB improves the throughput rate under a low WIP level. This study provides managerial insights for worker assignments and workload balancing. Article history: Received (21-MAY-2019); Revised (5-OCT-2019); Accepted (20-OCT-2019); Published online (1-NOV-2019)